Viruses and Viral Infections in Developing Countries - Jovanović-Ćupić, Snežana; Abubakar, Muhammad; Emel Önal, Ayşe; Kashif Saleemi, Muhammad; Božović, Ana; Krajnovic, Milena (IntechOpen, 2020)
This book contains information on various virus families, with the focus on viruses causing prevalent infections in parts of developing countries in Africa and Asia. Viral proteins play an important role in their replication and infection potential, and are the main candidates for antiviral therapy and vaccines. While some antiviral vaccines are available for quite some time (e.g. MMR), there are regions in the world still struggling with some infections. This is especially the problem in regions where the morbidity rate from viral infections among young children is high. This situation requires urgent measures to put infections under control.